Enhancement of Electrical Conductivity of Polyethylene Terephthalate (PET) Fabrics via Ionic Liquids. Issue 1 (2nd January 2019) - Seki, Yasemin
ABSTRACT: In this study, polyethylene terephtalate (PET) fabrics were treated with two types of ionic liquids, 1-ethyl-2, 3-dimethylimidazolium ethyl sulfate (EIL) and methyl-tri-n-butylammonium methyl sulfate (BIL), resulting in noticeably better long-term electrical conductivity of treated PET fabrics. Thermal conductivity, thermal stability, surface morphology and chemical structure were also explored. The effects of concentration of EIL (2, 6, 10 w/v %) and BIL (10, 15, 20 w/v %) ionic liquids were discussed. With the given set up, surface resistivities of the PET fabrics decreased with treatment application of the ionic liquids. Besides, BIL treatment provided higher electrical conductivity as compared with EIL. Moreover, surface resistivity presented diminishing tendency with increasing the concentration. It is also found that thermal degradation temperatures of the PET fabrics decreased with ionic liquids treatment. A coating layer was observable on surface of the fabric and in the gaps of the yarns with the ionic liquids treatment. This work provided a novel method for obtaining enhanced electrically conductive PET fabrics for textile industry. GRAPHICAL ABSTRACT: